Implementasi Nilai-nilai Berbhinneka Tunggal Ika dalam Pembelajaran Pendidikan Pancasila di SMP Negeri 6 Banjarmasin - Riska Aulia; Sarbaini Sarbaini; Alex Alex (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to describe the implementation of the values ​​of Bhinneka Tunggal Ika in school policies and culture, its application in the learning process, and analyze the supporting and inhibiting factors at SMP Negeri 6 Banjarmasin. This study uses a qualitative phenomenological approach with data collection techniques through observation, interviews, and documentation of the principal, three Pancasila Education teachers, and six students, through purposive sampling. Data analysis uses the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the values ​​of Bhinneka Tunggal Ika have been integrated into school policies and culture symbolically, institutionally, and participatory, as well as in learning through a collaborative approach and authentic assessment. However, there are still gaps in the internalization of values ​​in students and inconsistencies in assessment practices.